2009
DOI: 10.1016/s0004-9514(09)70056-x
|View full text |Cite
|
Sign up to set email alerts
|

Passive mobilisation of shoulder region joints plus advice and exercise does not reduce pain and disability more than advice and exercise alone: a randomised trial

Abstract: ACTRN 12605000080628.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 35 publications
2
46
0
1
Order By: Relevance
“…Individuals need to do the activities in newly gained range of motion to maintain motion at the joint. This result supports the findings of previous studies showing improvement after exercises in adhesive capsulitis [26].…”
Section: Abduction Rangessupporting
confidence: 93%
See 1 more Smart Citation
“…Individuals need to do the activities in newly gained range of motion to maintain motion at the joint. This result supports the findings of previous studies showing improvement after exercises in adhesive capsulitis [26].…”
Section: Abduction Rangessupporting
confidence: 93%
“…This result correlates with previous studies [24,26] which studied the effects of Maitland's ERM and exercises on subjects of adhesive capsulitis and found that besides pain and ROM function also improved.…”
Section: Abduction Rangessupporting
confidence: 92%
“…33 However, other studies have reported no significant differences for intensity of pain in SMT vs a sham group. 8,13 According to the pain intensity result from Chen et al, 34 our study did not report significant differences in pain intensity between groups. The magnitude of change in pain with impingement tests (Hawkins and Neer) identified in our study was similar Values are expressed as absolute and relative frequencies (n = 40) for categorical variables and as means ± standard deviations for continuous variables.…”
Section: Discussionmentioning
confidence: 46%
“…33,35 Some studies have reported that mobilizations in addition to exercise were not more effective in pain and disability than exercise alone. 34,36 In a comparative study of home exercises and supervised exercises for shoulder impingement, no differences between groups were identified in the intensity of pain, disability, physical activity and work, and active range of motion. 37 Nevertheless, surgery and exercises compared with a placebo laser have been reported to have statistical differences, 38 and an intervention with exercises produced higher improvement than shockwave therapy after 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Previous studies have found that 9-12 treatment sessions of passive joint mobilization has no additional benefit over exercise and advice in the short or long term, for improving function in patients with painful restricted shoulders of more than 1-months duration. 17,18 Similarly, the subjects in our study had symptoms for a similar time-frame, but the manual therapy treatment (MWM) comprised an active and passive movement component combined. 24 This approach was clearly more effective in the early management of our subjects with painful stiff shoulders.…”
Section: Discussionmentioning
confidence: 93%